Texica Limited (B) : human resource management committee - Maheshwari, Sunil Kumar; Ray, Prantika (London : Indian Institute of Management, Ahmedabad, 2017)
Texica Limited, a renowned textile company had been reporting losses for the past few years. The chairman, Mr. Ashutosh Verma decided to seek the help of Dr. Asim Vakil and his team of consultants to improve the performance of the company. The case is a continuation of Texica Limited (A) where Vakil recommended creating a human resource management committee to scrutinise all new hires for the county. The case follows a discussion of the human resource management committee as they debate whether they should hire a new brand manager.
Originally Published InMaheshwari, S. K., & Ray, P. (2017). Texica Limited (B): Human Resource Management Committee. HRM0239(B). Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Performance standards -- Case studies; Personnel management -- Case studies